PA.27 How can we improve mobilisation and response times?. (9th June 2014) - Kargbo, CA; Simpson, G; Thwaites, RJ
Abstract : Introduction: Neonatal transfer services provide babies with safe efficient transfers between neonatal units. 1 NICE recommends mobilisation times of 1 h1 hour for Time-Critical Emergencies (TCEs) and response times of 3.5 h from the start of referral calls. 1 NeTS Solent services were audited against NICE standards. Methods: Records of transfers between October and December 2013 were reviewed. Data concerning mobilising and response times of uplifts (transfers towards tertiary units) was analysed. Times were subdivided into 'decision', 'ambulance travel to base', 'loading up' and 'travel to referring hospital' to identify areas for improvement. Diagnoses and delay reasons were noted. Results: Nineteen of 38 uplifts were considered time-critical, by national or local criteria. Target mobilisation time was not met in 8 (4 national and 4 local). Target response time was not met in 2 but in both significantly delayed mobilisation was also noted. Conclusions: During this quarter, 42.1% of TCEs had mobilisation times exceeding one hour. In 62.5% of those transfers, 'decision' was the longest component. The remaining 37.5% were due to loading up time. Implementing decisions by 10 min would usually achieve target mobilisation times. We plan to re-audit soon. Reference: Toolkit for high quality neonatal care, DOH. http://www.dh.gov.uk/prod_consum_dh/groups/dh_digitalassets/@dh/@en/@ps/@sta/@perf/documents/digitalasset/dh_108435.pdf